2017
DOI: 10.1016/j.aott.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Peritendinous injection of platelet-rich plasma to treat tendinopathy: A retrospective review

Abstract: ObjectiveThe aim of this study was to determine factors associated with the likelihood of a better clinical outcome after the peritendinous injection of PRP for the treatment of chronic tendinopathy and identify whether PRP represents an effective treatment option for chronic tendinopathies.MethodsThe study included 214 patients (86 males and 128 females; mean age: 39.3 (18–75) years) who received PRP injections for tendinopathy refractory to conventional treatments. The mean duration of symptoms at the moment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 37 publications
1
7
2
Order By: Relevance
“…Our result matched with that of Unlu et al [25], which showed that injection of PRP around the tendon had beneficial clinical effects on improving subjective pain in patients who have tendinosis and tendon tear, with excellent tolerance.…”
Section: Discussionsupporting
confidence: 90%
“…Our result matched with that of Unlu et al [25], which showed that injection of PRP around the tendon had beneficial clinical effects on improving subjective pain in patients who have tendinosis and tendon tear, with excellent tolerance.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, platelet-rich plasma (PRP) has provided a new and encouraging therapy option for tendinopathy (Boesen, Hansen, Boesen, Malliaras, & Langberg, 2017;Smith & Sellon, 2014;Unlu, Kivrak, Kayaalp, Birsel, & Akgun, 2017). It is accepted that PRP can modulate tissue response to damage and stimulate tissue regeneration through release of growth factors (Wu, Diaz, & Borg-Stein, 2016), which act on angiogenesis, chemotaxis, and cell proliferation by activating related signal transduction pathways (Andia, Rubio-Azpeitia, & Maffulli, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…10 A retrospective study out of Turkey evaluating 214 patients who underwent PRP injection in various tendons found all tendinous locations had significantly lower VAS scores and higher perceived improvement in symptoms at 6 weeks and 6 months except for peroneal (12 patients) and Achilles (18 patients) tendons. 17 Given this procedure is often not covered by insurance providers and would be expected to carry the same risk of sural nerve irritation and intratendinous injection as other types of injections, we feel more data are needed regarding the safety and efficacy of this modality.…”
Section: Discussionmentioning
confidence: 99%